Capitalization of the Operating Experience of a Company for Sustainable Improvement: The Case of the ETRAG Foundry, Constantine, Algeria - Maamri, N.; Chaib, R.; Benidir, M.; Verzea, I. (Engineering, Technology & Applied Science Research, 2021)
Today, the adaptation to the effects of changing behavior and attitudes of Algerian companies has become a necessity. The current work aims to provide real-time information drawn from the field involvement with the use of performance indicators, in order to have a global vision of the general situation of the company. This allows for fulfilling functions such as awareness, guidance, decision support, and strategic planning. These indicators form a key data synthesis that affects all areas of the company’s affairs. Based on these indicators, a manager could have a better view of the business. Consequently, he could act effectively to correct the errors that have been revealed or continue in increasing the company’s development. This article describes the progress of management practices improvement in a foundry of the ETRAG company while relying on employee involvement. Through this work, the necessary preventive measures are established in the occupational environment ensuring the health and safety of employees. Thus, the well-being of the employees and the improvement of the working conditions can be assessed. The proposed work methodology consists of two components: the survey results obtained through a questionnaire in order to quantify the most exposed to risks and its intersection employees with the solutions proposed by the same employees. This approach aims at optimizing processes, instill a culture to the effects of changing attitudes and behaviors, to spread the culture of continuous and sustainable progress within a company, to ensure a good workplace atmosphere, and to have a respectful attitude towards employees.